Recognition Based upon the Vitality Criterion: A Key to Sustainable Economic Success - Brink, Alexander (Journal of business ethics, 2006)
Recognition is a basic precondition of participation. This article applies the dimension of recognition to business ethics. A case is made for normative stakeholder management as a voluntary commitment at the level of corporate leadership; this also meets management’s strategic demands. A vitality criterion is offered as a heuristic instrument, suggesting that any operation should be avoided which would violate the legitimate interests of stakeholders. For this reason, the recognition of mutually-conditioned stakeholder claims is understood as the central management idea.